Comparative Analysis of Post-Operative Analgesia Duration in Laparoscopic Cholecystectomy: Intraperitoneal Bupivacaine Versus Bupivacaine/Buprenorphine Combination: Bupivacaine Versus Buprenorphine in Laparoscopic Cholecystectomy - Hamza, Hasnain Ameer; Sarwar, Rabia; Aslam, Tayyeba; Sheikh, Raheel; Iqbal, Kashif; Zahra, Arooj (Pakistan Journal of Health Sciences, 2024)
Successful pain management following Laparoscopic Cholecystectomy (LC) is essential for a speedy recovery for patients. Intraperitoneal (IP) administration of analgesics, particularly bupivacaine and buprenorphine, offer promising approach to alleviate post-operative pain with minimized systemic side effects. Objective: To compare the duration of post-operative analgesia in patients undergoing laparoscopic cholecystectomy who receive either intraperitoneal bupivacaine alone or a combination of bupivacaine and buprenorphine. Methods: The quasi experimental study was conducted at Department of Anesthesiology, Farooq Hospital, Islamabad from April 2023 to September 2023. Patients scheduled for elective laparoscopic cholecystectomy for symptomatic cholelithiasis or other gallbladder diseases were included. The sampling methodology used was convenience sampling, with patients divided into two groups through the lottery method. Patients were assigned into two groups (55 patients in each group). Group A intraperitoneally received 25 ml dilution of bupivacaine (0.25%) in normal saline. Bupivacaine (0.25%) and buprenorphine (0.3mg) dissolved in normal ub6p B compared to Group A (9.26 ± 1.28 vs. 3.08 ± 1.04 hours, p < 0.001). Results: The mean BMI of participants was 29.79 ± 3.44 kg/m² Group A had 36 (65.5%) women and group B 41 (74.5%). The mean duration of post-operative analgesia was much greater in Group B (9.26 ± 1.28 hours vs. 3.08 ± 1.04 hours, p < 0.001). Conclusions: The combination of bupivacaine and buprenorphine offer post-operative analgesia in laparoscopic cholecystectomy with longer duration as compared to bupivacaine alone which is also statistically significant (p < 0.001).